2009
DOI: 10.1097/pgp.0b013e31817d9c61
|View full text |Cite
|
Sign up to set email alerts
|

DNA Hypermethylation Profiles in Squamous Cell Carcinoma of the Vulva

Abstract: Gene silencing through promoter hypermethylation is a growing concept in the development of human cancers. In this study, we examined the contribution of aberrant methylation of promoter regions in methylation-prone tumor suppressors to the pathogenesis of vulvar cancer. Thirteen cell lines from 12 patients with squamous cell carcinoma of the vulva (SCV) were evaluated for aberrant methylation status and gene copy number alterations, concomitantly, using the methylation-specific multiplex ligation-dependent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
(83 reference statements)
1
13
0
1
Order By: Relevance
“…These differences were marked by overall greater DNA methylation across the genic and other non-repetitive genome in HPV(+) cells compared to HPV(-) cells, also observed in a sample of primary tumors. LINE-1 methylation, a measure of global methylation, was also higher in HPV(+) cell lines and in a larger population of tumor specimens, consistent with the differences of two genes which had both higher methylation and higher expression in HPV(+): ESR1 (due to its significance and differential promoter methylation in other cancers), [28][29][30] and DCC (identified as biologically important in head and neck cancer). 31 Illumina Infinium platform data showed ESR1 and DCC average methylation of 4% and 10% in HPV(-) tumors compared to 82% and 87% respectively in HPV(+) tumors.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tsupporting
confidence: 51%
“…These differences were marked by overall greater DNA methylation across the genic and other non-repetitive genome in HPV(+) cells compared to HPV(-) cells, also observed in a sample of primary tumors. LINE-1 methylation, a measure of global methylation, was also higher in HPV(+) cell lines and in a larger population of tumor specimens, consistent with the differences of two genes which had both higher methylation and higher expression in HPV(+): ESR1 (due to its significance and differential promoter methylation in other cancers), [28][29][30] and DCC (identified as biologically important in head and neck cancer). 31 Illumina Infinium platform data showed ESR1 and DCC average methylation of 4% and 10% in HPV(-) tumors compared to 82% and 87% respectively in HPV(+) tumors.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tsupporting
confidence: 51%
“…ESR1 was chosen due to its significance and differential promoter methylation in other cancers (Archer et al, 2010; Heldring et al, 2007; Stephen et al, 2009). Additionally, Wisman et al identified more ESR1 promoter hypermethylation in cervical scrapings from cancer patients compared to normal subjects (64% versus 5.3% hypermethylated; p<0.0005) (Wisman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Analyses focused on three tumor suppressor genes, ESR1 (estrogen receptor 1), p16 (cyclin-dependent kinase inhibitor 2A) and DCC (deleted in colorectal carcinoma), based on reported associations of hypermethylation of these genes with either cervical cancer or cancers at other sites (Archer et al, 2010; Carvalho et al, 2006; Furtado et al, 2010; Heldring et al, 2007; Kim et al, 2010a; Stephen et al, 2009; Wisman et al, 2006). Specifically, the following candidate gene sites were examined in all participants for whom adequate DNA was available (n=151): 3 CpG sites in the ESR1 promoter region, 5 in an intronic region of DCC , and 4 in the promoter region of p16 .…”
Section: Methodsmentioning
confidence: 99%
“…The levels of the VHL transcript are increased in cervical carcinoma, which is the opposite of the demonstrated lower expression of VHL in renal cell carcinoma (49), multiple myeloma (50), pancreatic endocrine tumors (51), chronic lymphocytic leukemia (52) and squamous cell carcinoma of the vulva (53). The observed abnormal expression of VHL in cervical cancer could be associated with increased levels of HIF-1A, because we found a statistically significant, positive Spearman's rank correlation between HIF-1A and VHL expression.…”
Section: Normal Tissue Cancerous Tissue -----------------------------mentioning
confidence: 94%